Design of automotive composites - Lu, Y. Charles; Pilla, Srikanth (Society of Automotive Engineers. Electronic publications., 2014)
"Design of Automotive Composites reports that successful designs of automotive composites occurred recently in this arena. The chapters consist of eleven technical papers selected from the Automotive Composites and other relevant sessions that the editors have been organizing for the SAE International World Congress over the past five years. The composite design examples presented in Design of Automotive Composites come from the major OEMs and top-tier suppliers and are most relevant to the automotive materials challenges currently faced by the industry. Many of the innovative ideas have already been implemented on existing or new model vehicles, although a great deal of innovation is still in the works. With the advantage of supporting lightweighting and faster time to market, there is little doubt that composite materials can provide many tangible benefits and will become, over time, the material of choice for automakers."--